Effect of forging sequence and heat treatment on microstructure of high-duty power-plant shaft made of Cr-Mo ultra-high strength steel - Skubisz, Piotr; Lisiecki, Lukasz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The paper presents the results of modeling and testing of a heavy weight part made of Cr-Mo, which was V-modified ultra-high strength steel grade AISI 4140, processed through a novel open-die forging program and two alternative routes of two-stage heat treatment cycles designed to meet requirements of high-duty components for energy sector. By using unconventional forging conditions based on the assumption of large feed and reduction ratio and modifying the chemical composition, better control of the austenite grain was achieved to minimize abnormal grain growth and/or strain uniformity problems. Using the Finite Element Modeling, the multi-stage sequence of upsetting and the cogging strain distribution were optimized to minimize the strain variation along the length to a range 2.2÷2.7, and correlated with the microstructure generated at each main stage on the large cross-sections of the shaft. Machining cycles designed using the finite element method were fully verified physical modeling using a 16 ton forging block, including two alternative quenching strategies: oil vs. water spray and air. The material was studied in the as-forged, normalized and heat-treated states to observe the behavior of the hot-formed material and the effects of cooling conditions on the microstructure during the final heat treatment. It was found that the use of large feed ratios on cogging and varied cooling allowed to suppress the adverse effects of the inevitable abnormal grain growth, resulting in 1–2 ASTM in forged condition and reaching 6 ASTM and 8/9 ASTM after quenching in oil and water spray, respectively, which allowed a corresponding notched impact strength of 44÷48 and 85÷122 J/cm2 in the critical region of the forged shaft after tempering.